Wireless sensor networks lifetime assessment model development (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In the recent years low power computing systems have gained popularity.  Networks, which use low power computer systems and transmitted data by using wireless connection are called wireless sensor networks, which  main task is to get the information from sensors and transmission network. Nowadays, the most topical researches pertaining to wireless sensor networks are grounded on the  new optimization of structure of network transmission protocol, the routing optimization in transmission network, optimization of network structure, as a result of which the life circle of wireless network sensors is possible to increase. In the present article the methodology for determining the life circle of network is discussed. The approaches in detection of life circle pertaining to the important network nodes are described.